2013
DOI: 10.7196/samj.6677
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated neurocognitive disorders: Antiretroviral regimen, central nervous system penetration effectiveness, and cognitive outcomes

Abstract: Background. The human immunodeficiency virus (HIV) can give rise to a spectrum of neuropsychological impairments known collectively as HIV-associated neurocognitive disorders (HAND). Although antiretroviral therapy (ART) has reduced the incidence of HIV dementia, the prevalence of milder forms of HAND has increased. It has been postulated that incomplete central nervous system (CNS) viral suppression or potential drug toxicity, both of which could be related to the CNS penetration effectiveness (CPE) of ART re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…14,15 Moreover, observations from Guevara-Silva, Sacktor et al and Cross et al showed significant improvement in cognitive impairment after antiretroviral therapy in HIVinfected patients. [16][17][18] Functional alterations of the neurons by immunological and inflammatory changes due to HIVinfection may have role in the cognitive impairment. [19][20][21] Majority of the lesions observed in T1-weighted MRI was hypointense (70.6%).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Moreover, observations from Guevara-Silva, Sacktor et al and Cross et al showed significant improvement in cognitive impairment after antiretroviral therapy in HIVinfected patients. [16][17][18] Functional alterations of the neurons by immunological and inflammatory changes due to HIVinfection may have role in the cognitive impairment. [19][20][21] Majority of the lesions observed in T1-weighted MRI was hypointense (70.6%).…”
Section: Discussionmentioning
confidence: 99%
“…It goes without saying that advances made in antiretroviral treatment have transformed the disease into a chronic but manageable illness that enabled children to live longer with HIV. Although early initiation of cART has resulted in great improvements in survival, neurological consequences remain an important comorbidity among children living with HIV (7). The neuropathogenesis of HIV-associated neurocognitive disorder in the era of cART is complex and among others includes persistent systematic and central nervous system inflammation, oxidative stress, and HIV-subtype (clade) neurovirulence variation, associated with neuronal death and potential neurotoxicity of cART drugs (8).…”
Section: Introductionmentioning
confidence: 99%
“…In a later report, using a more comprehensive neuropsychological battery 76% of untreated HIV patients were classified as impaired (Joska et al 2011). A recent study of ART naïve HIV+ patients in South Africa (Cross et al 2013) found significant preservation or improvement in cognition following ART initiation, although the study was limited by the small number of participants available to adjust for practice effects.…”
Section: Introductionmentioning
confidence: 99%